2016
DOI: 10.20546/ijcrbp.2016.302.007
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Study of Some Threatened Plants in District Baramulla, Kashmir, Jammu and Kashmir, India

Abstract: In Kashmir valley, the plants have been used for treating various diseases from ancient times. About 700 plant species are being used as medicine in one or other form in Kashmir valley. This knowledge regarding the use of medicinal plants was transmitted from generation to generation orally. This traditional knowledge regarding the use of medicinal plants is draining off due to modernization. Also a number of plant species have been rendered threatened due to various anthropogenic as well as natural threats li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In different reports, it was documented that aromatic and medicinal plants are used for various therapeutic purposes [9][10][11]. It was reported that different plants species have been used in India for medicinal purposes and human nourishment since Vedic times [12]. Medicinal plants possess different types of phytochemicals, such as alkaloids, flavonoid and saponin.…”
Section: Introductionmentioning
confidence: 99%
“…In different reports, it was documented that aromatic and medicinal plants are used for various therapeutic purposes [9][10][11]. It was reported that different plants species have been used in India for medicinal purposes and human nourishment since Vedic times [12]. Medicinal plants possess different types of phytochemicals, such as alkaloids, flavonoid and saponin.…”
Section: Introductionmentioning
confidence: 99%
“…Since Vedic times, plants have been used for medicinal purposes and human sustenance in India. Rig Veda and Atharveda were the first to discuss the medicinal use of plants [ 13 ]. In India, approximately 75% of the population lives in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…According to Prabhu & Vijayakumar, 27 species of plants distributed in 27 genera belonging to 18 families were identified as commonly used ethno medicinal plants by ethnic people. Wani et al estimated 27 threatened plants along with their ethno botanical uses from District Baramulla, Kashmir, Jammu and Kashmir, India26 . Jan et al also investigated the same ethnobotanical study from Tehsil Tangi, District Charsadda27 .…”
mentioning
confidence: 99%